Atmospheric composition change: Climate–Chemistry interactions - Isaksen, I.S.A.; Granier, C.; Myhre, G.; Berntsen, T.; Dalsøren, S. B.; Gauss, M.; Klimont, Z.; Benestad, R.; Bousquet, P.; Collins, W.J.; Cox, T.; Eyring, Veronika; et al. (Atmospheric Environment, 2009)
Chemically active climate compounds are either primary compounds like methane (CH4), removed by oxidation in the atmosphere, or secondary compounds like ozone (O3), sulfate and organic aerosols, both formed and removed in the atmosphere. Man-induced climate–chemistry interaction is a two-way process: Emissions of pollutants change the atmospheric composition contributing to climate change through the aforementioned climate components, and climate change, through changes in temperature, dynamics, the hydrological cycle, atmospheric stability, and biosphere-atmosphere interactions, affects the atmospheric composition and oxidation processes in the troposphere. Here we present progress in our understanding of processes of importance for climate–chemistry interactions, and their contributions to changes in atmospheric composition and climate forcing. A key factor is the oxidation potential involving compounds like O3 and the hydroxyl radical (OH). Reported studies represent both current andfuture changes. Reported results include new estimates of radiative forcing based on extensive model studies of chemically active climate compounds like O3, and of particles inducing both direct and indirect effects. Through EU projects like ACCENT, QUANTIFY, and the AeroCom project, extensive studies on regional and sector-wise differences in the impact on atmospheric distribution are performed. Studies have shown that land-based emissions have a different effect on climate than ship and aircraft emissions, and different measures are needed to reduce the climate impact. Several areas where climate change can affect the tropospheric oxidation process and the chemical composition are identified. This can take place through enhanced stratospheric–tropospheric exchange of ozone, more frequent periods with stable conditions favoring pollution build up over industrial areas, enhanced temperature induced biogenic emissions, methane releases from permafrost thawing, and enhanced concentration through reduced biospheric uptake. During the ...